Peramalan Produksi Padi di Kota Padang Dengan Metode ARIMA - Putri Nabila; Saumi, Fazrina (Program Studi Matematika, Fakultas Teknik, Universitas Samudra. Langsa, Aceh., 2024)
Padang City, as one of the centers of economic growth in the region, has its own challenges and opportunities in managing rice production. Factors such as weather conditions, agricultural technology, and government policies can influence rice production. Therefore, using the ARIMA method can help related parties to respond to changing conditions more quickly and effectively. This research aims to apply the ARIMA method in predicting rice production in Padang City. By identifying historical patterns of rice production, it is hoped that patterns can be found that can be used as a basis for predicting future production. It is hoped that the results of this research can contribute to increasing the efficiency of rice production and supporting food security in this city. The data research method used in this research is monthly data on the amount of rice production in Padang City (in tons). Data on the amount of rice production was obtained from the Central Statistics Agency (BPS). This study focuses on rice production results in Padang City by utilizing rice production data from 2018 to 2022. The method applied in this research is the ARIMA method. The ARIMA model (2,1,1) is the best ARIMA model with the smallest MAPE value, namely 99% for forecasting rice production in Padang City. From the table of forecasting results, rice production in the city of Padang in 2023 is highest in December, namely 9.295 and the lowest in February, namely -39.0994. The forecast results are lower than the amount of rice production from the previous year.